PERFORMAAYAM MERAWANG YANG DIPELIHARA INTENSIF DI DAERAH BOGOR - Sri Yuniati Putri Koes Hardini; Santi Dewiki (Jurnal Matematika Sains dan Teknologi, 2003)
Merawang chicken is one of local chickensthat comes from Merawang region in the province of BangkaBelitung. It is one of the poultry that has good potentialto be used as egg producer and meat producer. There is a littleinformation about it However, the region where it comes from,it attracts a lot of attentions because it has promising potentials.The objective of this research is to identify performanceof Merawang chicken that raised in Bogor region. The resultsare the average of female body weight is 1234.1 grams, andfor the male is 1474.5 grams, length of shank is 9.7 cm andmortality is 9.6%.. The DOC weight is little bit bigger thanthat find in the original region. The results of performancewhich include body weight, length of shank, feed consumption,feed conversion and mortality are still good as produces inthe original region. Cost analyzes show that it is more benefitif the chickens used as layer than meat producer. This research gives useful additional informationon the existence of one of local chickens in Indonesia thathas potential for poultry husbandry